2020
DOI: 10.1016/j.jcot.2020.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Limb length discrepancy after total knee arthroplasty: Unilateral versus bilateral, a comparative study at tertiary centre

Abstract: Introduction:We conducted a prospective study to find out change in limb length (lengthening/shortening) after total knee arthroplsty in unilateral and bilateral total knee arthroplasty (TKA) because few literature is available regarding limb length discrepancy in TKA in comparison to total hip arthroplasty. Limb length discrepancy (LLD) may lead to low back pain and gait abnormalities. Material and methods: We divided 58 patients into two groups: Group A (28 patients) includes patients who underwent unilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Though these authors [ 2 ] state that LLD is significant, it may not be clinically important if patients do not appreciate a difference in their limb length. Moreover, a study states that patients only perceive a leg length change of 2 cm or more [ 12 ], suggesting that the majority of patients in our study would not perceive a difference in their limb length after surgery. Our findings suggest that limb lengthening occurs frequently after TKA, but not to a statistically significant extent.…”
Section: Discussionmentioning
confidence: 82%
“…Though these authors [ 2 ] state that LLD is significant, it may not be clinically important if patients do not appreciate a difference in their limb length. Moreover, a study states that patients only perceive a leg length change of 2 cm or more [ 12 ], suggesting that the majority of patients in our study would not perceive a difference in their limb length after surgery. Our findings suggest that limb lengthening occurs frequently after TKA, but not to a statistically significant extent.…”
Section: Discussionmentioning
confidence: 82%
“…predicted a limb length change of 4 mm for each 10-degree correction in HKA angle [ 10 ]. Accordingly, the more limb length change is expected in the developing and underdeveloped countries where the patients often visit at an advanced stage with extremes of deformity [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sabir et al . warned that unilateral TKA in bilaterally-affected OA knee might end up with significant LLD causing patient dissatisfaction and poor functional outcome [ 14 ]. In agreement with previous literature, this study also found that the functional outcome was adversely affected when LLD exceeded 10 mm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations